A Study on Ship Manoeuvring Simulation and Ship Trajectory Optimization Based on Sqp and Bfgs Algorithms from Sea Trials - Khanh Toan, Tran; ., . (International Journal of Engineering and Technology, 2018)
In this study, a procedure is proposed to optimize the shipâ€™s trajectory by identification of optimal hydrodynamic coefficients from sea trials, which coupled the dynamic ship motion model with optimization techniques. In order to assess efficiently the hydrodynamic parameters, a sensitivity analysis is first per- formed to identify the most sensitive coefficients, then an identification procedure, based on SQP and BFGS algorithms, is carried out to determine optimal hydrodynamic parameters. The validation of this procedure is done for Turning Circle and Zig-Zag tests by using experimental data of sea trials of the Esso Bernicia 193000DWT Tanker model. Comparisons between experimental and computed data show a fair agreement of overall tendency in ship trajectories. The RMSD (Root-Mean-Square Deviation) of ship trajectory decreases from 68.0m to 5.8m in Turning Circle test, and RMSD of yaw angle decreases from 17.3deg to 6.6deg in Zig-Zag test.Â Â Â